2017
DOI: 10.1021/acsnano.7b01064
|View full text |Cite
|
Sign up to set email alerts
|

Dipolar Molecular Capping in Quantum Dot-Sensitized Oxides: Fermi Level Pinning Precludes Tuning Donor–Acceptor Energetics

Abstract: Reducing the donor-acceptor excess energy (ΔG) associated with electron transfer (ET) across quantum dot (QD)/oxide interfaces can boost photoconversion efficiencies in sensitized solar cell and fuel architectures. One proposed path for engineering ΔG losses at interfaces refers to the tuning of sensitizer workfunction by exploiting QD dipolar molecular capping treatments. However, the change in workfunction per debye in QD solids has been reported to be ∼20-fold larger when compared to the effect achieved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…As a purely optical approach, THz spectroscopy can provide quantitative insight into the intrinsic charge-transport properties ( e.g., charge mobility, carrier density, etc. ) in the materials of interests in a contact-free fashion, which is particularly powerful for accessing the electrical properties of low-dimensional materials where electrical contacts are often challenging to deposit for conventional electrical studies. In a typical OPTP measurement, the EGs deposited on the fused silica (using the Langmuir–Schaefer method) are photoexcited by a short femtosecond (∼50 fs) laser pulse with a photon energy of ∼3.1 eV (400 nm) to generate charge carriers.…”
Section: Resultsmentioning
confidence: 99%
“…As a purely optical approach, THz spectroscopy can provide quantitative insight into the intrinsic charge-transport properties ( e.g., charge mobility, carrier density, etc. ) in the materials of interests in a contact-free fashion, which is particularly powerful for accessing the electrical properties of low-dimensional materials where electrical contacts are often challenging to deposit for conventional electrical studies. In a typical OPTP measurement, the EGs deposited on the fused silica (using the Langmuir–Schaefer method) are photoexcited by a short femtosecond (∼50 fs) laser pulse with a photon energy of ∼3.1 eV (400 nm) to generate charge carriers.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the inorganic coating layer treatment, photoanode interface modification with use of organic molecules was also demonstrated to be effective for the suppression of charge recombination. [480][481][482][483][484][485] For example, Mora-Seró and coworkers showed that molecular dipoles (DT) assisted ZnS treatment can give a better control of the recombination dynamics as well as the charge injection process. 480 TiO2/QD/electrolyte interface.…”
Section: Organic Molecular Treatmentmentioning
confidence: 99%
“…Finally, following our previous report, all QDs were molecularly passivated by 1,4-mercaptobenzoic acid, which substantially enhances the ET efficiency from QDs to oxide. 17,18,20 To unambiguously monitor HET, we have employed optical-pump THz-probe spectroscopy, which has been used extensively to quantify electron transfer rates and efficiencies for QD−oxide systems. 10,[17][18][19]21,22 Briefly, following selective optical excitation of QDs with a femtosecond optical laser pulse, the photoconductivity of the sample is monitored by a second pulse in the THz frequency range (0.4−2 THz), with a subpicosecond time resolution.…”
mentioning
confidence: 99%
“…17,18,20 To unambiguously monitor HET, we have employed optical-pump THz-probe spectroscopy, which has been used extensively to quantify electron transfer rates and efficiencies for QD−oxide systems. 10,[17][18][19]21,22 Briefly, following selective optical excitation of QDs with a femtosecond optical laser pulse, the photoconductivity of the sample is monitored by a second pulse in the THz frequency range (0.4−2 THz), with a subpicosecond time resolution. Immediately after excitation, the charge carriers are confined within the QDs, and the real conductivity is zero.…”
mentioning
confidence: 99%
See 1 more Smart Citation